Status of knowledge of the Malaysian herpetofauna - Das, I.; Yaakob, Norsham (2007)
Altogether, 203 species of amphibians and 397 species of reptiles are now known from Peninsular Malaysia and its offshore islands, and from East Malaysia (Sabah and Sarawak, and associated islands, on Borneo). Although a total of 600 herpetofaunal species seems a large figure in comparison to other landmasses of similar size regionally, a number of species have been discovered or recognized as new only in the last half a decade. Most of the new discoveries have been made from montane regions and offshore islands, but important findings have also been made not too far from the urban areas. Identification resources for the fauna specific to Peninsular Malaysia are relatively few, although recent field guides exist for all groups of taxa (except caecilians) for Borneo. No major systematic institutions exist within Malaysia for either type material or recent voucher specimens of herpetofaunal species, the Sarawak Museum in Kuching being repository of a small collection of mainly secondary types and older general collections from this state; the Selangor Museum in Kuala Lumpur was destroyed in the bombing of the city during World War II. Besides a concerted effort to continue inventories of Malaysia’s herpetofauna, urgently needed are the development of herpetology as a distinct discipline within the biological sciences of the university curriculum, and training of a generation of young biologists in relevant fields of systematics, ecology, genetics, biogeography, anatomy and morphology, in curatorship and an appreciation of the great outdoors